2021
DOI: 10.3855/jidc.12850
|View full text |Cite
|
Sign up to set email alerts
|

Detection of blaNDM-1 gene in ESBL producing Escherichia coli and Klebsiella pneumoniae isolated from urine samples

Abstract: Introduction: Enterobacteriaceae such as Escherichia coli and Klebsiella pneumoniae are the most prominent bacterial species resistant to almost all commonly used antibiotics. Carbapenem is one of the last resort drugs for treating such emerging multidrug-resistant bacteria. This study aimed to detect carbapenem-resistant blaNDM-1 gene in ESBL producing E. coli and K. pneumoniae isolates. Methodology: A total of 190 E. coli and 350 K. pneumoniae isolates were screened for extended spectrumβ-lactamase (ES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 0 publications
2
7
2
Order By: Relevance
“…The emergence of MBL-producing UTI-inducing E. coli isolates could be considered a serious threat to health communities because this pathogen is resistant to numerous antibiotics. In a study by Naeem et al [ 49 ], the NDM-positive rate was 38.5% (n = 10/26) among E. coli strains isolated from urine samples that was higher than the current result. In another study from Sudan [ 50 ], the bla VIM (16.7%) was the most prevalent MBL gene in clinical E. coli isolates followed by bla IMP (8.3%) and bla NDM (2.8%).There is a paucity of data regarding the bla VIM and bla IMP harboring UTI-causing E. coli in Iran.…”
Section: Discussioncontrasting
confidence: 72%
“…The emergence of MBL-producing UTI-inducing E. coli isolates could be considered a serious threat to health communities because this pathogen is resistant to numerous antibiotics. In a study by Naeem et al [ 49 ], the NDM-positive rate was 38.5% (n = 10/26) among E. coli strains isolated from urine samples that was higher than the current result. In another study from Sudan [ 50 ], the bla VIM (16.7%) was the most prevalent MBL gene in clinical E. coli isolates followed by bla IMP (8.3%) and bla NDM (2.8%).There is a paucity of data regarding the bla VIM and bla IMP harboring UTI-causing E. coli in Iran.…”
Section: Discussioncontrasting
confidence: 72%
“…as main producer species. Other reports from Pakistan supplement our findings that K. pneumoniae and E. coli were major contributors of the total carbapenemase production among Enterobacterales [ 15 , 17 , 40 , 44 , 57 , 90 , 91 ]. Another study observed a high proportion of carbapenemase production among Citrobacter spp.…”
Section: Discussionsupporting
confidence: 88%
“…Our results showed that the patients were infected mostly with K. pneumoniae and E. coli strains while infrequently detected genera were Pseudomonas, Proteus , Acinetobacter , Citrobacter , Morganella , Providencia and Burkholderia . Previous studies from Pakistan showed that K. pneumoniae and E. coli were the most commonly detected pathogens responsible for nosocomial infections [ 43 , 44 , 45 ]. While the global data suggested the higher prevalence of K. pneumoniae , P. aeruginosa , E. coli and A. baumannii from Tanzania, Algeria, Nepal and Saudi Arabia [ 46 , 47 , 48 , 49 ], our study demonstrated 42.1% CR among Enterobacterales .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we investigated the antimicrobial resistance profles, molecular typing, antibiotic resistance genes and plasmid replicon types of 45 consecutively collected CRKP isolates in Northern China. From the clinical department distribution, most of the CRKP isolates (48.9%, 22/45) originated from the ICU department and showed multidrug resistance, which was consistent with previous studies [23][24][25]. As K. pneumoniae is an opportunistic pathogen, ICU patients with impaired immunity are at an increased risk of infection.…”
Section: Discussionsupporting
confidence: 88%